Connectivity Through Routes: Strengthening the Relationship between India and Bangladesh - Gaur, Neetu and Vijay Laxmi (2011)
The paper explores the cooperative path followed by South Asia in general and the two nations, India and Bangladesh in particular since 1971, point at the shortcomings in the cooperative development process, explore potential areas of cooperation between India and Bangladesh, and suggest a way ahead. Main focus of this paper is on the developments in the areas of connectivity before and after the joint communiqué signed by the Prime Minister of India and Prime Minister of Bangladesh in January 2010.